Innovative Functional Fruit Leather from Bidara Fruit and Citrus Peel with Carrageenan for Sustainable Food Processing - Caroline Noel Amaris Purnomo; Karyn Gracia Hartono; Karla Katina Salim Nohkarsan (Soegijapranata Catholic University, 2025)
Concerns about food waste and the need for sustainable functional food has been growing and therefore led to the search for fruit based functional snacks that are formulated with natural ingredients and also low environmental impact. This review aims to search for the potential of the use of bidara fruit (Ziziphus mauritiana), arabic gum, citrus peel, and carrageenan as a functional fruit leather. Thus, this review fills the gap by integrating underutilized local fruits (bidara) and food industry by-products (citrus peel) with natural hydrocolloids (carrageenan) into a sustainable and functional snack formulation. Literature with year limitations from the last five years was analyzed using databases such as Google Scholar and PubMed with keywords searched such as